Sustainable tourism, deforestation and growth: a case for Malaysia - Habibullah, Muzafar Shah; Din, Badariah; Choo, Wei Chong; Tan, Siow Hooi (Penerbit Universiti Malaysia Terengganu, 2019)
Sustainable tourism perceived as a significant driver of income and creates job opportunities for local communities, which, as a result, deliver significant incentives to preserve biodiversity. Preserving the quality of environment becomes the prime concern to attract more tourists, which as a result, increase funds for biodiversity conservation. Massive increase in tourism together with limited environmental resources capacity, there is an urgent need to raise the awareness on the issue of biodiversity for tourism development. For the purpose of this research, we examine the impact and economic growth on sustainable tourism for the period 1996 – 2012 in Malaysia. For the purpose of this study, we construct a Sustainable Tourism Index (STI) and employed few methods which are the Ordinary Least Squares (OLS), Canonical cointegrating regression (CCR), Dynamic OLS (DOLS) and Fully-Modified OLS (FMOLS) methods to test the long-run model of sustainable tourism. Generally, our results found that economic growth and mitigating do contribute to sustainable tourism in Malaysia.